Technology Attributes Stimulating Learner Behaviors and Outcomes of Language Learning - Hee-Jung Jung (English Language Teaching, 2019)
This study examined factors that may influence learners' technology integration for language learning. The use of technology is rapidly growing in English language learning. To reflect this trend, numerous studies have focused on learners’ achievement in technology-integrated language learning environments. However, research on EFL learners’ use behaviors with technologies for learning English remains scarce. To achieve this study’s aims, the proposed research model incorporated technology factors (flexibility, mobility, interaction/communication, andinformation resources) and learner behaviors (attitude, motivation, and self-regulation) into perceived effectiveness and perceived efficiency. Data collected from a survey of university students were analyzed to test the proposed hypotheses using the structural equation modeling(SEM). The analysis showed that all proposed hypotheses with exception of H2a and H4a were significant at p<0.01. This paper concludes with a discussion of the academic and practical implications of the study’s findings. KCI Citation Count: 0